How to create animation in 10 easy lessons - Bishop-Stephens, Will (Super skills (Irvine, Calif.), 2016)
"So you want to be an animator, but you don't have your own million-dollar studio? Don't let that stop you! From learning how to make a simple flip book to creating stop-motion claymation, you'll soon learn the many ways you can make great animated movies in your own home"--Back cover.